Use of big data analytics for small and medium sized businesses - Chernova, Olga A.; Mitrofanova, Inna V.; Pleshakova, Marina V.; V. Batmanova, Victoria (Serbian Journal of Management, 2023)
Small and medium sized business has an important place in the economy of all countries. In modern conditions of Industry 4.0 development, the introduction of big data analytics into the performance of small and medium-sized businesses can become the basis for sustainability growth of their functioning and their competitive advantages’ development. However, the use of Big Data technology is not typical for small and medium enterprises. At the same time, the issues of big data analytics use by small and medium-sized businesses in the context of their resource and infrastructure constraints are poorly studied. The purpose of this article is to develop a conceptual model for the implementation of big data analytics in the activities of small and medium-sized businesses, taking into account their digitalization problems. The study was made on the basis of the Russian economy data. The analysis of the issues of big data analytics’ use for small and medium-sized businesses was based on the methodology of system analysis with the identification of object, environment and project-process development subsystems. The novelty of research consists in the fact that the development model of the structure of big data use was carried out in accordance with the content of the main tasks that must be solved within data management life cycle. The results of the study showed that the main issues of the introduction of big data analytics in the activities of small and medium-sized businesses are associated with a lack of understanding of its benefits by entrepreneurs. Also significant problems are the lack of financial resources and the lack of qualified employees capable of strategic administration of these processes. Given these problems, the authors conclude that the model for use of big data analytics by small and medium-sized businesses should be based on the use of cloud software and analysis of projects with open source big data. The article suggests the structure of the model for big data use by small and medium-sized businesses. This paper contributes to the development of ideas about the directions of digitalization of small and medium-sized businesses in order to increase the sustainability of this economic sector in the context of Industry 4.0. Further research by the authors is connected with effectiveness evaluation of mechanisms and tools of government support made for digital business transformations.